In vivo response to starch-based scaffolds designed for bone tissue engineering applications - Salgado, A. J. (2007)
Our purpose was to evaluate the in vivo endosseous response to three starch-based scaffolds implanted in rats (n ¼ 54). We implanted the three scaffold groups; a 50/50 (wt %) blend of corn starch and ethylene-vinyl alcohol (SEVA-C), the same composition coated with a biomimetic calcium phosphate (Ca-P) layer (SEVA-C/ CaP), and a 50/50 (wt %) blend of corn starch and cellulose acetate (SCA), all produced by extrusion with blowing agents, into distal femurs proximal to the epiphyseal plate, for 1, 3, or 6 weeks. Our results showed that at 1 week considerable reparative bone formed around all scaffold groups, although the bone was separated from the scaffold by an intervening soft tissue interfacial zone that comprised two distinct compartments: the surface of the scaffold was occupied by multinucleate giant cells and the compartment between these cells and the surrounding bone was occupied by a streaming fibrous-like tissue. The extracellular matrix of the latter was continuous with the extracellular bone matrix itself, labeled positively for osteocalcin and appeared mineralized by backscattered electron imaging. All three scaffolds showed a similar tissue response, with the soft tissue interface diminishing with time. No bone contact was observed with SEVA-C at any time point, only transitory bone contact was observed with SEVA-C/CaP at 3 weeks, but SCA exhibited direct bone contact at 6 weeks where 56.23 6 6.46% of the scaffold surface was occupied by bone. We conclude that all materials exhibited a favorable bony response and that the rapidly forming initial ‘‘connective tissue’’ seen around all scaffolds was a very early form of bone formation.